The Effectiveness of Two Proposed Strategies Based on Information Gathering Skills in the Achievement of Students in the Department of Educational and Psychological Sciences in the Foundations of Education Course - Ghadban, Hussein Ali; Khamis, Tariq Hashem (Journal of Tikrit University for Humanities, 2023)
The study aimed at the effectiveness of two proposed strategies based on the skills of collecting information in the achievement of students of the Department of Educational and Psychological Sciences in the subject of foundations of education. Two experimental groups were chosen for the study, the strategies of Building and Integration (45) male and female students, and the control group (45) male and female students. The approaches used in this paper are the t-test for two independent samples, Pearson's correlation coefficient, as well as the chi-square. The study reached a set of results as follows: The experimental groups outperformed the control groups in achievement.